Mitigasi Kebencanaan Pada SMA Negeri 14 Ambon Sebagai Upaya Pengurangan Resiko Bencana Gempa Bumi - Berli Isreal Titahena; Eka Sasmitha; Mei Anista Ririmasse; Bervi Latuserimala; Samsul Bahri Loklomin; Novita Berhitu (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
This activity focuses on the socialization and simulation of earthquake disaster mitigation at SMA Negeri 14 Ambon. The aim was to increase students' awareness and preparedness in facing disasters, especially earthquakes. The methods used included material presentations using PowerPoint and simulations. This activity was attended by high school students with an age range of 15-18 years, who are at an ideal stage of cognitive development to receive and apply knowledge about disaster mitigation. The results showed that students had high enthusiasm and a good understanding of earthquake disaster mitigation after attending the socialization. This activity succeeded in increasing students' knowledge about actions to be taken before, during and after a disaster occurs. In conclusion, disaster mitigation socialization at the high school level is a strategic step in building a disaster resilient community. This activity can be a model for the development of similar programs in other schools, supporting the government's efforts in building community resilience to disasters.